Phosphorus esters of 1‐dopyl‐1, 2‐(4‐hydroxyphenyl)ethene as effective flame retardants for polymeric materials. (5th October 2020) - Howell, Bob A.; Lienhart, Gavan W.
Summary: 1‐Dopyl‐1, 2‐(4‐hydroxyphenyl)ethene has been converted to phosphorus diesters, 1‐dopyl‐1, 2‐(4‐diphenylphosphatophenyl)ethene (BDE‐DPP), and 1‐dopyl‐1, 2‐(4‐dopyloxyphenyl)ethene (BDE‐DOPO) which have been fully characterized using spectroscopic and thermal methods and assessed as flame retardants in DGEBA epoxy (diglycidyl ether of bisphenol A). Both are effective flame retardants. The ester containing diphenylphosphato groups (BDE‐DPP) acts primarily in the condensed phase while that containing only dopyl units acts predominately in the gas phase. DGEBA epoxy containing sufficient 1‐dopyl‐1, 2‐(4‐dopyloxyphenyl)ethene to provide 2% phosphorus displays a limiting oxygen index of 28, a peak heat release rate of 506 W/g, and a total heat release of 24 kJ/g.